Suitability of groundwater of Dabaa region –Iraqi western desert for agricultural use - Ahmad M.Al-alwany, Abdulkarem (Iraqi Journal of Civil Engineering, 2016)
The study included evaluating water ten wells in the area Dabaa within the western region of Iraq for agricultural use, as has been the study of water quality of these wells during the year by conducting a full analysis of water samples and assess suitability for irrigation depending on the standard specifications of the Food and Agriculture Organization. As the analysis results showed that all the studied wells located within the water of light to moderate in terms of the seriousness of Electrical conductivity if used for irrigation, and sodium adsorption ratio values for all water wells studied were within the Has no influence soil permeability. It turned out that the Toxic Effect of these water plants were mild to moderate effect for sodium either chloride was degree selection of non-toxic to light moderate, and that the use method Piper for the classification of water showed that it quality predominantly Na+, Mg +2, Ca+2 - Mg+2 , Ca+2 for positive ions and water quality sulphurous HCO3-, SO4 = predominantly basal in terms of negative ions.